2019
DOI: 10.1093/icc/dtz004
|View full text |Cite
|
Sign up to set email alerts
|

The patent paradox in crowdfunding: an empirical analysis of Kickstarter data

Abstract: Building on signaling theory, this paper analyzes whether projects signaling patented technologies have a higher probability of funding success on a reward-based crowdfunding platform as compared to a control group of similar projects. Our analysis of a set of Kickstarter projects suggests the existence of an apparent paradox concerning the role of patents in this funding context. Despite solid evidence in entrepreneurial finance literature on the positive role of patents for accessing financing from professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Usually, investors do not possess the skills required for assessing the projects and technologies proposed by the entrepreneur, while entrepreneurs tend to be reluctant about revealing all the information about the proposed products/technologies and their potential on the market. Consequently, it is difficult for investors to identify the information they need to assess the quality of start-ups and to distinguish between promising and unprofitable investments (Meoli et al, 2019 ). The matter of asymmetry is very important in crowdfunding campaigns that are carried out online for a short period of time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Usually, investors do not possess the skills required for assessing the projects and technologies proposed by the entrepreneur, while entrepreneurs tend to be reluctant about revealing all the information about the proposed products/technologies and their potential on the market. Consequently, it is difficult for investors to identify the information they need to assess the quality of start-ups and to distinguish between promising and unprofitable investments (Meoli et al, 2019 ). The matter of asymmetry is very important in crowdfunding campaigns that are carried out online for a short period of time.…”
Section: Resultsmentioning
confidence: 99%
“…Meoli et al ( 2019 ) have studied the role of patents in the attraction of investors in reward-based crowdfunding . Unlike professional investors, such as venture capitalists, for whom holding a patent for the product to be developed via the start-up is a favorable argument for financially supporting the project, in the case of backers the authors identified that this aspect correlates negatively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These open models of collaboration include many actors who gained increasing importance in collaborating with firms during the OI era, such as Startups, Spinoffs, Venture capitalists, Employees, Lead users, Individuals, Inventors, Innovators, and, among all, Universities. In particular, since the diffusion of the Technology Transfer Offices, university efforts to commercialize science have evolved (Kochenkova et al, 2016), and new pathways are emerging, such as the spin-off creation based on research results (Munari et al, 2016), crowdfunding of entrepreneurial projects (Meoli et al, 2019), and an interesting novel approach relates to the activation of OI initiative (Enkel et al, 2009). Over the years, several companies have used Hackathons (Mohajer Soltani et al, 2014) and other OI forms to generate creative ideas (Dahlander and Wallin, 2020), involving universities in their programs.…”
Section: Open Innovation (Oi)mentioning
confidence: 99%